Use of conventional business intelligence (bi) systems as the future of big data analysis - Majid, Molla E; Marinova, Dora; Hossain, Amzad; Chowdhury, M.E.H.; Rummani, F. (Science and Education Publishing Co. Ltd, 2024)
Traditional Business Intelligence (BI) systems employ a combination of source systems, databases, data repositories, data warehouses, and analytical tools to gain insights into business operations and chart future organizational strategies. These BI systems typically rely on structured data extracted from the underlying source system databases. However, organizations are increasingly harnessing vast amounts of big data from diverse sources, which often include semi-structured and unstructured data. The BI systems currently in use were initially designed with structured organizational datasets in mind. As the volume of big data required for informed decision-making continues to grow, a pressing question arises: can the existing BI systems effectively analyse this diverse and expansive data landscape? This research seeks to assess the adaptability of current BI systems to analyse big data and presents potential strategies for addressing this evolving data landscape.